EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI SIKLUS PENDAPATAN DENGAN PROGRAM IRIS MENGGUNAKAN PENDEKATAN METODE SYSTEM DEVELOPMENT LIFE CYCLE - Muhammad Rofiq Sunarko, Genta Kusumaningdiyah, Dewi Saptantinah & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The purpose of this research is to get information and analyze about the accounting information system of sales and cash receipts at Togamas Solo Book Store. The data analysis performed in this study using the method of the System Development Life Cycle (SDLC), while steps are identifying parts of the organization, activities and related documents in the revenue cycle, making the system documentation in the flowchart form, performance evaluation system, and proposed improvements system. This study using interviews, observation, and documentation. The questions in this study addressed to the store manager and organizations section that related to the revenue cycle which includes cash sales, credit sales, cash receipts from cash sales and cash receipts from the credit sales. The results of this study indicate that the accounting information system applied in the revenue cycle of Togamas Solo Bookstore still found weaknesses in passwords, the existence of dual authority, and their employees who have a double function.Keywords: accounting information system, method system develompent life cycle